Dile benden ne dilersen - Gutman, Dan.; Santat, Dan; Epsilon (İstanbul : Epsilon, 2012)
The students in a fifth-grade class at Lincoln School in Oak Park, Illinois, must learn to work together quickly when a meteorite crashes into their classroom and the genie inside grants them a Christmas wish--if they can agree on one within an hour.
School Library Journal
4.8
3-6.
3-6
Turkish
Keywords: Christmas -- Fiction; Genies -- Fiction; Meteorites -- Fiction; Schools -- Fiction; Wishes -- Fiction; Christmas -- Fiction; Genies -- Fiction; Meteorites -- Fiction; School stories; Wishes -- Fiction